EVALUATING MEDICATION ADHERENCE THROUGH HOME MEDICATION REVIEWS IN THE PAEDIATRIC COMMUNITY: A CROSS-SECTIONAL STUDY. - Abbas, Zahir; Ahmad, Ghazi Shariq; Pugalia, Rishabh (Student's Journal of Health Research Africa, 2024)
Background: Medication adherence is vital for managing chronic conditions in pediatric populations, with community pharmacist-led home medication reviews showing promise in improving adherence and outcomes. However, they require careful consideration of pediatric-specific challenges and needs. The study aimed to evaluate medication adherence through home medication reviews in the pediatric community. Methods: A cross-sectional study was conducted over one year. One hundred participants aged 18 years and below, undergoing medication for any illness, were included. Data on socio-demographic characteristics, presenting symptoms, medical histories, diagnoses, treatments, and outcomes were collected using a custom-designed instrument. Statistical analysis was performed using Microsoft Excel 2019. Results: The study of 100 pediatric participants (52% males, 65% aged 16-18) found an 80% symptom improvement post-treatment and an 85% overall medication adherence rate. Home medication reviews increased adherence by 15%, with higher rates in chronic conditions like asthma (90%) compared to acute conditions (80%). Participants and caregivers reported improved medication understanding and reduced errors, with rural participants showing notable adherence improvements (70% to 85%). Conclusion: Home medication reviews significantly improved medication adherence in pediatric patients, increasing overall adherence rates by 15%. The intervention was particularly effective for chronic conditions like asthma. Participants showed symptom improvement, and both patients and caregivers responded positively. These findings highlight the value of pharmacist-led home medication reviews in enhancing adherence and health outcomes in pediatric care. Recommendations: Advocate for integrating community pharmacist-led home medication reviews into pediatric care, tailor interventions for socio-demographic factors, foster collaboration among healthcare providers, and conduct further research on their long-term effectiveness and cost-effectiveness.